B biotype of Bemisia tabaci (Hemiptera: Aleyrodidae): crop pest of pepper in the Cauca Valley, Colombia - RODRÍGUEZ T., ISAURA V.; BUENO M., JUAN M.; CARDONA M., CÉSAR; MORALES M., HÉCTOR (Revista Colombiana de Entomología, 2012)
To identify the distribution of Bemisia tabaci biotype B in pepper crops in the Cauca Valley, Colombia, adult and pupal samples were taken from thirty-three sites in 12 different locations visited. Initial differentiation between the species Bemisia tabaci and Trialeurodes vaporariorum was based on morphological characteristics of the fourth instar (pupae). Reconfirmation of species identity and identification of biotypes was done by means of random amplified polymorphic DNA (RAPD’s-PCR analysis). The dominant species was B. tabaci B biotype, which was recorded in 50% of the samples. The A biotype of B. tabaci was not detected and a mixture of biotype B and T. vaporariorum was found in 31.2% of the samples. Levels of insecticide resistance were studied in adults and first instar nymphs of the B biotype, across six sites of the department with the methodologies and diagnostic doses previously established by CIAT. In addition, line base data, LC50, LC90 and diagnostic doses for thioxiclam hydrogen oxalate on adults and pyriproxifen and spiromesifen on first instar nymphs were calculated using the leaf-dip methodology. Adult populations showed high levels of resistance to methamidophos, and some cases of intermediate resistance to cypermethrin, imidacloprid and thioxyclam hydrogen oxalate. The nymphs from locations with excessive use of insecticides have shown intermediate resistance to imidacloprid, buprofezin and diafentiuron. The implications of these results in the management of insect in pepper crops are discuss.